Analisis Pengaruh Religiusitas dan Literasi Keuangan Syariah terhadap Minat Masyarakat Pekanbaru menjadi Nasabah Bank Syariah Indonesia (BSI) - Lamby Mahdalena Mirawati; Delima Afriyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of Islamic banking in Indonesia is currently experiencing rapid growth, in line with increasing public awareness of the importance of financial systems that comply with Sharia principles. One of the Islamic banking institutions that continues to develop is Bank Syariah Indonesia (BSI) in Pekanbaru City. However, in reality, there are still some members of the public who are not fully interested in becoming customers of Islamic banks, which is influenced by the level of religiosity and understanding of Islamic financial literacy. The purpose of this study is to determine the effect of religiosity and Islamic financial literacy on public interest in becoming customers of Bank Syariah Indonesia in Pekanbaru City. This study employs a quantitative approach using purposive sampling technique. The data used in this study are primary data with a total sample of 400 respondents. Data collection was conducted through the distribution of questionnaires. Data processing was carried out using SPSS software, with analysis techniques including descriptive analysis, validity test, reliability test, multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination). The results of the study indicate that religiosity and Islamic financial literacy partially have a positive and significant effect on public interest, and simultaneously also have a positive and significant effect on public interest in becoming customers of Bank Syariah Indonesia in Pekanbaru City.